Nutrition in neonatal congenital heart disease - Morgan CT; Shine AM; McMahon CJ (Dove Medical Press, 2013)
Conall T Morgan,1 Anne Marie Shine,2 Colin J McMahon1 1Department of Pediatric Cardiology, 2Department of Clinical Nutrition and Dietetics, Our Lady's Children's Hospital Crumlin, Dublin, Republic of Ireland Abstract: There are 40,000 infants born in the USA with congenital heart disease annually. Achievement of adequate oral nutrition is difficult in this population. Malnutrition is common. Single ventricle physiology, the risk of necrotizing enterocolitis, and cardiopulmonary bypass prevent the establishment of normal oral feeding patterns. Improved nutrition results in improved surgical outcomes, lower mortality, and shorter hospital stay. In this review, we discuss the challenges this population faces. Keywords: necrotizing enterocolitis, malnutrition, growth failure, hypoplastic left heart